Examination of optimum test conditions for a 3-point bending and cutting test to evaluate sound emission of wafer during deformation - Erdem Carsanba; Gerhard Schleining (International Journal of Food Studies)
The purpose of this study was to investigate optimum test conditions of acoustical-mechanical measurement of wafer analysed by Acoustic Envelope Detector attached to the Texture Analyser. Forcedisplacement and acoustic signals were simultaneously recorded applying two different methods (3-point bending and cutting test). In order to study acoustical-mechanical behaviour of wafers, the parameters “maximum sound pressure”, “total count peaks” and “mean sound value” were used and optimal test conditions of microphone position and test speed were examined. With a microphone position of 45° angle and 1 cm distance and at a low test speed of 0.5 mm/s wafers of different quality could be distinguished best. The angle of microphone did not have significant effect on acoustic results and the nu